Counsellor Supervision: An Exploratory Study of The Metaphoric Case Drawing Method of Case Presentation In A Clinical Setting - Stone, Daniel; Amundson, Norman (Canadian Journal of Counselling and Psychotherapy, 2011)
This study investigated the efficacy of the Metaphoric Case Drawing (MCD) method of counsellor supervision. The context of the study was intensive small group supervision in a crisis intervention and suicide prevention setting. Five core counselling areas were under investigation. These were client dynamics, the counsellor's role, the client-counsellor relationship, counselling goals, and case presentation effectiveness. With the Metaphoric Case Drawing method, supervisors and counsellor-trainees reported a substantial increase in understanding compared with the more traditional Verbal Case Debriefing (VCD) method. Statistical and qualitative data further confirmed the effectiveness of the MCD method. The Metaphoric Case Drawing method was found to be particularly effective for case presentations including themes of depression, suicide, relationship problems, and manipulative clients.